2022
DOI: 10.1093/hr/uhac128
|View full text |Cite
|
Sign up to set email alerts
|

The bHLH transcription factor AcB2 regulates anthocyanin biosynthesis in onion (Allium cepa L.)

Abstract: Onion bulb color is a key breeding trait. The red bulb color is caused by the presence of anthocyanins, which are products of the flavonoid synthesis pathway. Research on flavonoid regulation in onion is lagging compared with that in other crops. AcB2 encodes a bHLH transcription factor, and its transcription is positively associated with anthocyanin accumulation and correlated with the expression of AcMYB1, which is an activator in the flavonoid biosynthetic pathway in onion. Phylogenetic analysis showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…GtMYBP3 and GtMYBP4 regulate genes involved in early biosynthesis of avonoids and promote avonol biosynthesis [43]. The bHLH transcription factor AcB2 has been shown to interact with AcMYB1 and increase anthocyanin biosynthesis in onion [44]. After our KEGG analysis, there were 20 bHLH and six MYB genes annotated into the avonoid pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GtMYBP3 and GtMYBP4 regulate genes involved in early biosynthesis of avonoids and promote avonol biosynthesis [43]. The bHLH transcription factor AcB2 has been shown to interact with AcMYB1 and increase anthocyanin biosynthesis in onion [44]. After our KEGG analysis, there were 20 bHLH and six MYB genes annotated into the avonoid pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A series of repressors of anthocyanin biosynthesis have been identified over the past decade, including the MYB, SPL, miRNA, HD‐ZIP, LBD, NAC, and TCP proteins (Albert et al, 2014; Chen et al, 2019a; LaFountain and Yuan, 2021). Many studies have reported the positive regulatory role of bHLH TFs in anthocyanin biosynthesis in a variety of species, while the exploration of anthocyanin repressors in the bHLH family has been neglected (Nesi et al, 2000; Robbins et al, 2003; Ohno et al, 2011; Xie et al, 2012; Li et al, 2022). Although recent studies have reported that bHLH1 is a repressor of anthocyanin biosynthesis in Chimonanthus praecox and eggplant (Zhao et al, 2020; Duan et al, 2021), the anthocyanin repressors in the bHLH family remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…GtMYBP3 and GtMYBP4 regulate early biosynthesis genes of flavonoids, FNS and F3’H , and promete flavonol biosynthesis (Nakatsuka et al ., 2012). AcB2, a bHLH transcription factor, had been reported to interact with AcMYB1 and increase anthocyanin biosynthesis in onion (Li et al ., 2022). After our KEGG analysis, there were 20 bHLH and six MYB genes annotated into the flavonoid pathway (Fig 5b, c).…”
Section: Discussionmentioning
confidence: 99%